Retrospective case study of livestock diseases recorded at Fulbaria upazila veterinary hospital in Mymensingh district of Bangladesh - Akter, R; Soltana, T; Nisa, N; Rahman, T; Islam, M R; Hossain, M M; Alam, J (Bangladesh Journal of Animal Science, 2024)
The present study was undertaken to find out the suspected livestock cases recorded in upazila veterinary hospital from October 1, 2021, to November 30, 2022. The data were collected from the registered book that was maintained at the upazila livestock office. We found that cattle, goats, chickens, ducks, and pigeons were common livestock species taken to veterinary hospitals. We also found that clinical cases of animals were treated based on clinical history, clinical signs, and physical examination and diseases were grouped as infectious and non-infectious diseases in cattle and goats, diseases of chicken, duck, and pigeons. The relative ratio of occurrence of lumpy skin diseases and peste des petitis ruminants was high among other infectious diseases in cattle and goats respectively. By contrast, the relative ratio of occurrences of non-infectious bloat was high among other non-infectious diseases in cattle and goats. We also found that clinical cases in poultry were treated based on clinical history, clinical signs, physical examination, and postmortem examination and were grouped as diseases in chickens, ducks, and pigeons. The relative ratio of occurrences of visceral gout, duck viral enteritis, and pigeon pox was high among other diseases in chicken, duck, and pigeon respectively during the study period. In summary, the findings have indicated the various clinical cases, diagnoses, treatment approaches, and incidence in livestock species at Fulbaria upazila veterinary hospital of Mymensingh district of Bangladesh. Bangladesh Journal of Animal Science 53(4): 135-143, 2024